Hubungan Pengetahuan Kesehatan Reproduksi Remaja Dengan Kebersihan Daerah Kewanitaan di SMAN 1 Dolok Batu Nanggar Kabupaten Simalungun - Pardede, Desika Wali (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Lack of knowledge in adolescents related to health can result in a lack of hygiene in their intimate areas, which can later have a negative impact on their reproductive health. This study aims to determine the relationship between adolescent reproductive health knowledge and hygiene in women's areas at SMAN 1 Dolok Batu Nanggar, Simalungun Regency. This study is a quantitative study. This study uses primary data taken using a survey method with a previously prepared questionnaire as a measuring tool. This questionnaire consists of several modified statements taken from several previous studies with reference to the theoretical basis related to the research variables. The research sample is the Simple Random Sampling technique. The sample size of this study was calculated using the Slovin formula. The sample in this study was 36 female students of class XI IPS SMAN 1 Dolok Batu Nanggar, Simalungun Regency. The results of the bivariate test or statistical test using the chi-square test through the Fisher Exact Test obtained a p-value of 0.000 <0.05. Analysis of the research results found that there was a relationship between adolescent reproductive health knowledge and feminine hygiene in SMA Negeri 1 Dolok Batunanggar. The majority of female students in grade XI IPS of SMA Negeri 1 Dolok Batunanggar had good knowledge of reproductive health. The majority of female students in grade XI IPS of SMA Negeri 1 Dolok Batunanggar had a good understanding of feminine hygiene.